Outcome analysis and risk factors for postoperative colonic ischaemia after aortic surgery - Dovzhanskiy, Dmitriy I.; Bischoff, Moritz; Wilichowski, Christopher Daniel; Rengier, Fabian; Klempka, Anna; Böckler, Dittmar (Langenbeck's archives of surgery, 2020)
Colonic ischaemia (CI) represents a serious complication after aortic surgery. This study aimed to analyse risk factors and outcome of patients suffering from postoperative CI.